(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article considers the state of innovative development of Ukraine in the period from 2012 to 2016, in particular, the dynamics of indicators of innovative activity of enterprises is analyzed, sources and structure of expenses for financing innovative activity is investigated. It was found that the share of enterprises engaged in innovations during the studied period was of a changing nature. The decrease of this indicator was the result of the crisis in the economy. The main obstacle to the innovative development of the economy is the low technical and technological level of production due to the considerable wear and tear of existing equipment. At the same time, the total amount of research spending has more than doubled since 2012. The indicators of innovation implementation were investigated, regions with the highest share of innovative enterprises were identified. Special attention is paid to staffing of research activities. The high level of scientific capacity of the country is highlighted.